USING YOUTUBE TO IMPROVEEFL READING COMPREHENSION AMONG VOCATIONAL - Nuramah Hayikaleng; Subadrah Madhwa Nair; Hariharan N Krishnasamy (Proceedings of The ICECRS, 2016)
In Thailand, YouTube has not been widely used for educational purposes especially in Narathiwat. The purpose of  this  study was to  investigate  the  effects of using YouTube  on EFL reading comprehensionamong vocational students. A  quasi-experimental  design  was  adopted.  Two  groups  of  first  year  vocational students at Narathiwat Technical College were purposefully assigned to the experimental and the control groups. The instruments used in this study were pre-test and post-test. Students in the experimental group were taught reading comprehension using YouTube and the students in the control group were taught using conventional method. The results showed positive effects of using YouTube. Therefore, YouTube  should be considered  as  an  effective  instructional  tool  for  improving English reading comprehension and as an important teaching resource in English classrooms.